A new postural balance control system for rehabilitation training based on virtual cycling. - Chul Gyu Song (IEEE Transactions on information technology in biomedicine)
A new rehabilitation training system was developed to improve postural balance control by combining virtual reality technology with an unfixed bicycle. Twenty healthy subjects participated in the present study by riding the virtual cycling system under two different conditions: with or without visual feedback. Data were collected on the following parameters: path deviation, cycling velocity, etc. As a result of conducting the repeated training, results showed improvement not only in the ability to control balance and weight shift but also in the overall cycling ability including the degree of path deviation and the cycling speed. It was concluded that the system was effective as a training device and, in addition, the technology might have a wider applicability to the rehabilitation field.